Application of Online Learning Class Management Through Reward and Punishment - Sri Marmoah; Daru Nafisyah Ichlasita; Hadiyah Hadiyah (Al-Hayat: Journal of Islamic Education, 2022)
Rewards and punishments are needed so that learning in class runs smoothly and there are no significant problems. This study aims to describe the application of classroom management through reward and punishment in the online learning process in Class II Integrated Islamic Elementary School (SDIT) Al Hasna Klaten from an Islamic perspective. The research approach used is descriptive qualitative research. The data in this study are the results of interviews with a class teacher and six students’ second grade of SDIT Al Hasna Klaten, observations, and documentation. The data sources in this study were a class teacher and six second-grade students and the online learning process at SDIT Al Hasna Klaten. The data analysis technique in this study used interactive analysis techniques consisting of data collection, data reduction, data presentation, and conclusion. The validity of the data was tested by observing the persistence and triangulation of data sources. The results showed that at the planning, implementation, and evaluation stages of classroom management, rewards were given directly in the form of a positive response from the teacher by providing praise, emoticons, and other forms of added value. Children in the online learning process. In contrast, the punishment given by the teacher is entirely appropriate and wise in the form of warnings and additional assignments to students so that students continue to achieve good learning outcomes. In addition, punishment is given in a way that students are asked to do good things to make up for their mistakes, such as giving charity, istighfar (prayer), and apologizing. The results of this study can contribute to the improvement of online learning.